Increased Frequency of Circulating Follicular Helper T Cells in Children with Hand, Foot, and Mouth Disease Caused by Enterovirus 71 Infection. (11th June 2014) - Wu, Jianping; Cui, David; Yang, Xianzhi; Lou, Jianzhou; Lin, Jie; Ye, Xianfei; Qin, Zhimei; Huang, Li; Zhao, Dejian; Huo, Zhaoxia; Xie, Guoliang; Zheng, Shufa; et al.
Abstract : Enterovirus 71 (EV71) is a major causative agent of hand, foot, and mouth disease (HFMD) in children. The role of T follicular helper (TFH) cells in EV71-infected children remains unclear in regulating humoral immunity. The frequency of circulating ICOS high /PD-1 high CXCR5 + CD4 + TFH cells in the children with mild and severe EV71 infection and healthy controls (HC) was detected by flow cytometry, respectively. IL-21 and IL-6 mRNA expression and their serum levels, Bcl-6 mRNA expression, and specific neutralizing antibodies against EV71 (NAb-EV71) were measured. In the acute stage of patients with EV71 infection, increased frequencies of circulating TFH cells with ICOS high and PD-1 high expression in the mild and severe patients were observed, and the positive correlations among the frequencies of circulating TFH cells and the serum levels of IL-21, IL-6, and NAb-EV71 titres were detected, respectively. Moreover, the expressions of IL-6 and IL-21 mRNA in PBMCs from patients were also significantly higher than those of HC. However, further analysis did not reveal any significant differences between mild and severe patients. These data indicate a role of TFH cells and associated cytokines in modulating the humoral response during the pathogenesis of EV71 infection.